Megalithic sites in Punang Kelapang, Upper Baram, Sarawak: a preliminary survey - Nicholas Gani (Ikatan Ahli Arkeologi Malaysia, Universiti Kebangsaan Malaysia, 2019)
Most of what is presently known about megalithic remains in Sarawak have come from research conducted in the Kelabit Highlands, in the Upper Baram. Another area in the Upper Baram where megalithic remains are known to be present is Punang Kelapang, south of the Kelabit Highlands. Compared to their counterparts in the Kelabit Highlands, however, much less is known about the megalithic remains in Punang Kelapang. In order to obtain more information about the megaliths in Punang Kelapang, an archaeological survey was conducted over a period of about five-and-a-half weeks in March, April and August 2016. This article presents the results of the survey. A total of twenty megalithic sites were recorded, out of which fourteen were visited. The megaliths in Punang Kelapang consist of megalithic cemeteries such as dolmens, stone jars, stone trough, cist graves, and rock burials; and non-cemetery megaliths such as stone mounds, carved stones and a standing stone.